Do Different Tooth Bleaching–Remineralizing Regimens Affect the Bleaching Effectiveness and Enamel Microhardness In Vitro? - Hamideh Sadat Mohammadipour; Parnian Shokrollahi; Sima Gholami; Hosein Bagheri; Fatemeh Namdar; Salehe Sekandari (International Journal of Dentistry)
Objective. Tooth bleaching may negatively affect the enamel surface properties, such as reduction in hardness values, and remineralizing agents can reverse these effects. This study evaluated the effect of remineralizing agents before, during, and after the bleaching process on enamel’s whitening effectiveness and microhardness. Methods and Materials. The initial color of 104 bovine incisors after immersion in tea solution was recorded, and then, the teeth were randomly divided into eight groups (n = 13). Group 1 (NC) was considered the control with no treatment, and Group 2 (B) was bleached with 40% hydrogen peroxide gel. The 3% fluorohydroxyapatite (FHA) and 2% sodium fluoride (NaF) were applied before (FHA/B, NaF/B), during (FHA + B, NaF + B) and after (B/FHA, B/NaF) the bleaching process in other groups. The final color and microhardness in three depths of 20–30, 50–60, and 100–120 µm were measured. Data were analyzed using Shapiro–Wilk, one-way ANOVA, Tukey, Games Howell, repeated measurement, and LSD tests. Results. The FHA + B presented the lowest ΔE, significantly lower than other groups, except B/FHA. The ΔE in B/FHA was significantly lower than B/NaF. The bleaching significantly reduced the enamel hardness in three depths. The highest microhardness values were reported for B/NaF and NaF + B, which have no noticeable difference with NC, while FHA/B showed the lowest hardness in three depths, which was significantly lower than NC. Conclusion. The application of NaF before, during, and after the bleaching improved the microhardness of bleached enamel as the unbleached one with no adverse effect on whitening effectiveness.